Instructional Management Strategy: A Multi-Sites Study on Science Teaching for Islamic School - Abdul Ghofur; Nahdia Rupawandi BR; Abdul Kholiq Ahmad (Journal of Educational Science and Technology (EST), 2017)
This paper describes how management strategies in science learning are done by teachers in Islamic schools. This is motivated by the ranking of Indonesia which 87 percent of the population of Muslims always occupy the lowest position for the ability of science literacy. This research was conducted for four months using descriptive qualitative design with data collection technique of interview, observation and documentation. The subjects of the study were six Islamic schools in Lamongan, East Java. The six Islamic schools were chosen by purposive sampling. The results showed that the learning activities of science more dominated by teachers, students heard more explanation than the practice in verifying the process of science. The majority of teachers use lecture, question and answer methods, and assignments, and occasionally apply discussion and demonstration methods. Science laboratories in schools have not been maximally used, some have limited tools and materials, some of which lack laboratory space and even two schools without a science laboratory. Assessment of student learning progress done through pretest, posttest, daily test, question and answer during lessons, UTS and UAS. Teacher's strategy in managing student learning motivation by using animated video as apperception, integrating science materials with Islamic religious values.